A critical analysis of the lexical description of נצל and ישׁע in the Hebrew bible—with some perspectives from cognitive semantics - Hornea, Irina Carina (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.